Analisis Yuridis Upah di Bawah Upah Minimum sebagai Hitungan Pesangon Pemutusan Hubungan Kerja yang Diputus oleh Pengadilan Hubungan Industrial - Kohar, Kohar; Irayadi, Muhamad (HUMANIORUM, 2025)
Wages are the rights of workers/laborers received and stated in the form of money as compensation from employers or employers to workers/laborers, as happened to worker Neni Kartika who was paid wages below the minimum wage of Bogor Regency in 2021 and during work there was a dispute related to the employment relationship which resulted in Termination of Employment, therefore Worker Neni Kartika filed a lawsuit for Termination of Industrial Relations Dispute to the Industrial Relations Court, but the Panel of Judges issued a Decision in which the severance pay for termination of employment was calculated based on wages below the minimum wage of Bogor Regency in 2021, because the Panel of Judges was of the opinion that it had been agreed upon by the PT. Sung Bo Jaya Workers Union with PT. Sung Bo Jaya regarding the wages, it is very clear that it is very contrary to the labor law where the Wages agreed upon by the PT. Sung Bo Jaya Workers Union with PT. Sung Bo Jaya have nothing to do with worker Neni Kartika because Wages are Workers' Rights and there is no agreement between Worker Neni Kartika or the GSPMII PT. Sung Bo Jaya Workers Union with PT. Sung Bo Jaya, the problem arises, namely How are Workers'/Laborers' Wage Rights in Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation and How are Wages below the Minimum Wage As a calculation of severance pay, using the research method used by the author is Normative legal research, namely research on the application of law, and the author concludes that the Panel of Judges' considerations are wrong and do not carefully apply the law in providing their legal considerations.